Villreinens verden (Wild reindeer) by Eigil Reimers - Skjenneberg, Sven (Rangifer, 1990)
Eigil Reimers: «Villreinens verden». (Wild reindeer). H. Aschehoug & Co. (W. Nygaard), Oslo, 1989. 126pp. ISBN 82-03-15859. NOK 298,-. (In Norwegian)